Hubungan Personal Hygiene Genetalia Dengan Kejadian Keputihan Pada Remaja Santri Putri Di Pondok Pesantren Al – Qur’an Harsallakum Kota Bengkulu - Pradina, Gia; Yulianti, Syami; Putri, Yesi (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Vaginal discharge is a common reproductive health issue among adolescent girls, particularly in boarding school environments. The World Health Organisation (WHO) reports that 75% of women have experienced vaginal discharge, with poor genital hygiene being one of the contributing factors. This study aims to investigate the relationship between genital hygiene and the occurrence of vaginal discharge. The study employed an analytical method with a cross-sectional approach, involving 59 respondents selected using total sampling technique. Data collection was conducted using a questionnaire that included questions about genital hygiene habits and experiences of vaginal discharge. Univariate analysis results showed that most respondents had poor genital hygiene (44.1%) and experienced vaginal discharge (47.5%). The chi-square test results indicated a significant association between genital hygiene and vaginal discharge (p = 0.002). It is hoped that boarding schools can optimise education and counselling on personal hygiene and vaginal discharge to prevent vaginal discharge among female students.